HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN KONTROL BEROBAT PADA KLIEN GANGGUAN JIWA DI POLI RAWAT JALAN RSJ PROF. DR. MUHAMMAD ILDREM MEDAN - Rusmauli Lumban gaol; Imelda Derang (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Mental disorders are changes in attitudes and behavior in an extreme person from attitudes and behaviors that can cause suffering and can hurt oneself, do not show empathy for others and can harm others, people with mental disorders usually do not realize that their behavior is deviant and also shows the ability of self-control which is very lacking, if this ability of self-control is seriously lacking it is said to be a mental disorder. The purpose of this study was to determine the relationship between family support and compliance with outpatient control in clients with mental disorders at the Outpatient Clinic of RSJ Prof. Dr. Muhammad Ildrem Medan. This study uses correlation analytic with cross section approach. The sample in this study was conducted on 60 respondents of mental disorders client families who came for outpatient treatment at the Poli clinic RSJ Prof. Muhammad Ildrem Medan. The statistical results showed p value = 0.029 (p <0.05) with a confidence level of 95%. This shows statistically that there is a relationship between family support and compliance with outpatient control in clients with mental disorders. Changes in the attitude and behavior of someone who is extreme from attitudes and behaviors that can cause suffering and can hurt oneself, do not show empathy for others and can harm others, people with mental disorders usually do not realize that their behavior is deviant and also shows ability very lack of self-control.